Prescaling and far-from-equilibrium hydrodynamics in the quark-gluon plasma - Mazeliauskas, Aleksas; Berges, Jürgen (Physical review letters, 2019)
Prescaling is a far-from-equilibrium phenomenon which describes the rapid establishment of a universal scaling form of distributions much before the universal values of their scaling exponents are realized. We consider the example of the spatiotemporal evolution of the quark-gluon plasma explored in heavy-ion collisions at sufficiently high energies. Solving QCD kinetic theory with elastic and inelastic processes, we demonstrate that the gluon and quark distributions very quickly adapt a self-similar scaling form, which is independent of initial condition details and system parameters. The dynamics in the prescaling regime is then fully encoded in a few time-dependent scaling exponents, whose slow evolution gives rise to far-from-equilibrium hydrodynamic behavior.
Gesehen am 30.07.2019